Coleccion Fotografica del Museo Nacional de Bellas Artes. - Facio, Sara; Glusberg, Jorge (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1998)
Agosti, Paola ; Althouse, Stephen ; Alvarez Bravo, Manuel ; Batho, Claude ; Bigio, Raquel ; Bischof, Werner ; Blok, Diana ; Boubat, Edouard ; Brandt, Bill ; Bravo, Lola Alvarez ; Cartier-Bresson, Henri ; Casals, José ; Catany, Toni ; Charbonnier, Jean Philippe ; Clergue, Lucien ; Dieuzaide, Jean ; Doisneau, Robert ; Eleta, Sandra ; Facio, Sara ; Faucon, Bernard ; Fontana, Franco ; Fontcuberta, Joan ; Freund, Gisèle ; Gar ; Gibson, Ralph ; Grellaud, Alejo ; Heinrich, Annemarie ; Kertesz, André ; López, Marcos ; Maniel, Javier Silva ; Michals, Duane ; Navarro, Rafael ; Neto, Mario Cravo ; Newman, Arnold ; Orive, Maria Cristina ; Otero, Pedro ; Paillet, Fernando ; Palma, Luis Gonzalez ; Parra, Liliana ; Rivas, Humberto ; Rodero, Cristina Garcia ; Roger, Dominique ; Saderman, Anatole ; Sandro, Juan Di ; Sieff, Jeanloup ; Sougez, Emmanuel ; Stern, Grete ; Stieglitz, Alfred ; Travnik, Juan ; Witcomb, Alejando S. ; Witcomb, Estudio ; Wolk, Alejandro ; Yanpolsky, Marianne ; Zimmermann, Marcos
spaans
boek